Perceived Stress, Causes of Stress and Coping Strategies among UniKL RCMP Undergraduate Students during COVID-19 Pandemic - Farizul Asman Johari; Aina Amanina Abdul Jalil; Nor Safwan Hadi Nor Afendi (Asian Journal of Medicine & Health Sciences, 2022)
Background: During the coronavirus disease (COVID-19) pandemic, people face many physical and social distancing consequences, which significantly affects students. University students have experienced emotional stress as a result of fulfil the university’s increasing demands for assignments and tests, as well as and a variety of distractions during online classes. This study aims to identify perceived stress, causes of stress, and coping strategies among Universiti Kuala Lumpur Royal College of Medicine Perak (UniKL RCMP) students during the COVID-19 pandemic. Methods: A total of 325 respondents participated in this cross-sectional study which was conducted by distributing online questionnaires through Google form via various platforms. Descriptive analysis was used to assess respondents’ level of perceived stress and identify the causes of stress and coping strategies. Chi-square test was also used to identify the association between sociodemographic profiles with the level of perceived stress, causes of stress and respondents’ coping strategies. P-value